Prospects and Challenges of Brain Gain from ASEAN Integration - Sheila V. Siar (Philippine Institute for Development Studies (PIDS), 2014)
This paper suggests that the ASEAN economic integration can be viewed as an opportunity for brain gain for the ASEAN member-countries. The envisaged ASEAN Economic Community (AEC) may boost both South-South and North-South movements of skilled labor as a result of the growth of cross-border education, increased mobility of professional workers with the implementation of the mutual recognition arrangements, and the possible return migration of expatriate professionals to the ASEAN region given a vibrant regional economy in the long run that can provide more competitive remuneration packages. In turn, these will facilitate knowledge exchanges and collaborations, technology transfers, economic and business linkages, investment flows, and increased remittances. However, the more advanced economies in the region will have an edge in exploiting these opportunities in the initial years of the AEC. The ASEAN integration can be a double-edged sword for member-countries that may not be able to improve their competitiveness in the long run.
Keywords: 330; brain gain; ASEAN Economic Community (AEC); brain drain; cross-border education; mutual recognition arrangements; return migration